Are immigrants in Canada over‐represented in riskier jobs relative to Canadian‐born labor market participants?. Issue 9 (14th June 2015) - Tiagi, Raaj
<x xml:space="preserve">Abstract</x> Background This paper uses new data to examine the gap in injury and fatality rates between immigrant men and women and their Canadian‐born counterparts. Methods Data from the 2011 National Household Survey and the Association of Workers′ Compensation Boards of Canada were used to determine the difference in occupational and industry injury and fatality rates between various arrival cohorts of immigrants and those Canadian born. Results For both men and women, there is no significant difference in occupational injury and fatality rates between various arrival cohorts of immigrants and Canadian‐born workers. However, industry injury and fatality rates are lower for the most recent arrival cohorts of immigrants relative to Canadian‐born workers. Conclusions Although immigrants face many hurdles and challenges in their resettlement process in Canada, given the evidence from the paper, they are not likely to be at higher risk for work‐related injuries relative to those Canadian‐born. Am. J. Ind. Med. 58:933–942, 2015. © 2015 Wiley Periodicals, Inc.